IMMU-05. SAFETY AND EFFICACY OF INTRAVENTRICULAR 131I-LABELED MONOCLONAL ANTIBODY 8H9 TARGETING THE SURFACE GLYCOPROTEIN B7-H3. Issue 2 (22nd June 2018) - Kramer, Kim; Kushner, Brian; Modak, Shakeel; Taskar, Neeta Pandit; Tomlinson, Ursula; Donzelli, Maria; Wolden, Suzanne; Zanzonico, Pat; Humm, John; Haque, Sofia; Souweidane, Mark; Greenfield, Jeffrey; et al.
Abstract: BACKGROUND: Tumors metastasizing to the CNS are associated with significant mortality. We tested the toxicity and dosimetry of intraventricular 131 I-labeled monoclonal antibody 8H9 targeting B7-H3 in patients with CNS tumors. METHODS: Tumor B7-H3 expression was assessed by immunohistochemistry. Patients received 2 mCi tracer of intra-Ommaya 124 I- or 131 I-8H9 followed by a therapeutic injection (10-80 mCi, dose levels 1-8 in 10 mCi increments -phase I patients; expanded cohort 50 mCi/injection) 131 I-8H9. Dosimetry was based on serial CSF, blood samplings and ROI analyses on nuclear imaging. . Toxicity was defined by the CTCAE v.3.0. Repeat injections were permitted if no serious adverse events or progressive disease ensued. Tumor response was determined by clinical, radiographic, cytologic criteria; overall survival was noted. RESULTS: 131 patients received 383 injections [median age 5.4 years (1.2- 53.6)] Injections were well tolerated. Rare self-limited adverse events included grade 1 or 2 fever, headache, vomiting, biochemical elevations in AST/ALT and 1 injection with grade 3 ALT elevation (dose level 3)., Myelosuppression occurred in patients with prior craniospinal radiation and at dose levels 6 and higher (>60 mCi). Of 93 patients treated for CNS neuroblastoma, an improved overall survival was noted compared to survival reported with conventional therapies. Interpatient variability for total absorbed dose to the CSF and blood was observed; mean absorbed CSF dose was 104.9 cGy/mCi by CSF sampling, and 2.6 cGy/mCi to the blood. CONCLUSIONS: Intraventricular 131 I-8H9 is safe, has favorable dosimetry to CSF, and has clinical utility for high risk primary and metastatic CNS tumors.